Identifying fetal alcohol spectrum disorder among South African children at aged 1 and 5 years. (1st December 2020) - Wynn, Adriane; Rotheram-Borus, Mary Jane; Davis, Emily; le Roux, Ingrid; Almirol, Ellen; O'Connor, Mary; Tomlinson, Mark
Highlights: Screening positive for FASD more than doubled from 1.5 years to 5 years of age (from 6.8 % to 14.8 %). With free transportation and repeated scheduling, mothers fail to get second stage screening for FASD with a physician. Better family integration with primary healthcare is required for early diagnosis and intervention for FASD. Abstract: Background: Fetal Alcohol Spectrum Disorders (FASD) are a global health concern. Early intervention mitigates deficits, yet early diagnosis remains challenging. We examined whether children can be screened and meet diagnoses for FASD at 1.5 years compared to 5 years post-birth. Methods: A population cohort of pregnant women in 24 neighborhoods (N = 1258) was recruited and 84.5 %–96 % were reassessed at two weeks post-birth, 0.5 years, 1.5 years, 3 years, and 5 years later. A two-step process was followed to diagnose FASD; first, a paraprofessional screened the children and then a physician evaluated the child. We evaluated FASD symptoms at 1.5 vs. 5 years. We also examined maternal differences in children receiving a positive FASD screening (n = 160) with those who received a negative FASD screening. Results: Screening positive for FASD more than doubled from 1.5 years to 5 years (from 6.8 % to 14.8 %). About one quarter of children who screened positive and were evaluated by a physician, were diagnosed as having a FASD. However, half did not complete the 2nd stage screening. Compared to mothers of children with a negative FASD screening, mothers of children with a positive FASD screening were less likely to have a high school education and more likely to have lower incomes, have experienced interpersonal partner violence, and have a depressed mood. Mothers of children who did not follow up for a 2nd stage physician evaluation were more like to live in informal housing compared to those who followed-up (81.3 % vs. 62.5 %, p = 0.014). Conclusions: We found that children can be screened and diagnosed for FASD at 1.5 and 5 years. As FASD characteristics develop over time, repeated screenings are necessary to identify all affected children and launch preventive interventions. Referrals for children to see a physician to confirm diagnosis and link children to care remains a challenge. Integration with the primary healthcare system might mitigate some of those difficulties.